2012
DOI: 10.1152/ajpregu.00081.2012
|View full text |Cite
|
Sign up to set email alerts
|

Central adenosine receptor signaling is necessary for daily torpor in mice

Abstract: When calorically restricted at cool ambient temperatures, mice conserve energy by entering torpor, during which metabolic rate (MR), body temperature (T(b)), heart rate (HR), and locomotor activity (LMA) decrease. Treatment with exogenous adenosine produces a similar hypometabolic state. In this study, we conducted a series of experiments using the nonspecific adenosine receptor antagonists aminophylline and 8-sulfophenyltheophylline (8-SPT) to test the hypothesis that adenosine signaling is necessary for torp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 41 publications
5
52
1
Order By: Relevance
“…The iNTS contains a dense localization of A1ARs (Carrettiero and Fior-Chadi, 2004;Pickel et al, 2006) and a potent inhibition of BAT SNA and BAT thermogenesis follows nanoinjection of the GABA A antagonist bicuculline into the iNTS (Cao et al, 2010). To determine the potential role of an activation of BAT sympathoinhibitory neurons in iNTS in the hypothermic, torporlike state induced by intracerebroventricular administration of CHA, we tested the hypothesis that iNTS neurons are activated (i.e., express c-fos) during the hypothermia evoked by intracerebroventricular CHA.…”
Section: Nts Neurons Are Activated By Intracerebroventricular Adminismentioning
confidence: 99%
See 1 more Smart Citation
“…The iNTS contains a dense localization of A1ARs (Carrettiero and Fior-Chadi, 2004;Pickel et al, 2006) and a potent inhibition of BAT SNA and BAT thermogenesis follows nanoinjection of the GABA A antagonist bicuculline into the iNTS (Cao et al, 2010). To determine the potential role of an activation of BAT sympathoinhibitory neurons in iNTS in the hypothermic, torporlike state induced by intracerebroventricular administration of CHA, we tested the hypothesis that iNTS neurons are activated (i.e., express c-fos) during the hypothermia evoked by intracerebroventricular CHA.…”
Section: Nts Neurons Are Activated By Intracerebroventricular Adminismentioning
confidence: 99%
“…Indeed, central A1 adenosine receptor (A1AR) activation is necessary for the induction and maintenance of natural torpor (Jinka et al, 2011;Iliff and Swoap, 2012), and central administration of adenosine 5Ј-monophosphate (AMP) elicits a marked, A1AR-dependent hypothermia in mice (Muzzi et al, 2013). Although expressed throughout the CNS, adenosine receptors are strongly localized in the intermediate nucleus of the solitary tract (iNTS) (Carrettiero and Fior-Chadi, 2004;Pickel et al, 2006), the primary termination site of visceral afferents controlling cardiovascular, respiratory, gustatory, and metabolic function (Andresen and Kunze, 1994;Grill and Hayes, 2012). Indeed, the iNTS has received considerable attention for its role in the regulation of body temperature and metabolism (Székely, 2000;Cao et al, 2010;Grill and Hayes, 2012;Kong et al, 2012) and iNTS neurons are in a unique position to integrate central and peripheral energy-related signals (Blevins et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms that mediate these changes are poorly understood, but recent studies have demonstrated that in small mammals, adenosine receptors are key in initiating and maintaining (i) the HMR, (ii) decreases in T b and (iii) the entry into torpor. In support of this, adenosine receptor agonism decreases metabolism and T b , and induces entry into a torpor-like state in rats and arctic ground squirrels [6,7], whereas adenosine receptor antagonism prevents or reverses these changes in hibernating arctic ground squirrels [7,8], and during intra-day torpor or fasting-induced torpor in mice [9][10][11] and rats [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has long been observed that adenosine induces hypothermia in a dose-dependent manner in mice [118][119][120]. Furthermore, the adenosine A1 receptor may play a key role because A1 receptor agonists other than adenosine also induce hypothermia [120,121]. Adenosine is neuroprotective against stroke and elicits multiple protective mechanisms [122][123][124].…”
Section: Adenosine and Adenine Nucleotidesmentioning
confidence: 99%
“…Through one or more steps of dephosphorylation, ATP can be sequentially degraded to adenosine diphosphate (ADP), adenosine monophosphate (AMP), and adenosine. It has long been observed that adenosine induces hypothermia in a dose-dependent manner in mice [118][119][120]. Furthermore, the adenosine A1 receptor may play a key role because A1 receptor agonists other than adenosine also induce hypothermia [120,121].…”
Section: Adenosine and Adenine Nucleotidesmentioning
confidence: 99%